Holy Bible. [compact disc, unabridged] Historical books of the Old Testament, part 4. - Dietz, Norman; Runger, Nelson (Recorded Books, LLC, 2004)
Word-for-word unabridged recording of 1 Chronicles and 2 Chronicles, narrated in contemporary language for easy understanding.